A technological, pedagogical, arts knowledge framework. Issue 3 (2nd July 2016) - Jensen, Amy Petersen
ABSTRACT: This article invites media arts and technology educators to find synergies in their classroom curriculum and practice. Encouraging the use of the National Media Arts Standards it summons teachers to develop a useful framework for technological practice that utilizes arts knowledge and pedagogies.